Hesperetin Induces Autophagy and Delayed Apoptosis by Modulating the AMPK/Akt/mTOR Pathway in Human Leukemia Cells In Vitro - Ching-Yeh Lin; Ya-Hui Chen; Ying-Chih Huang (Current Issues in Molecular Biology, 2023)
Background: Hesperetin has been reported to have anticancer properties. However, the molecular mechanisms underlying its action on leukemia cells remain unclear. This in vitro study evaluated the possible mechanisms of hesperetin in leukemia cells (HL-60 and U937). Methods: Cell viability was evaluated using a cell counting kit-8 (CCK-8) assay. Apoptosis and autophagy assays were conducted through annexin V/PI staining and acidic vesicular organelle (AVO) staining. Cell cycle analysis was conducted through propidium iodide (PI) and flow cytometry. The expression of proteins related to apoptosis and autophagy, including cleaved-PARP-1, Bcl-2, Bax, LC3-I/II, Beclin-1, Atg5, p62, phospho-AMPK, AMPK, phospho-mTOR, mTOR, phospho-Akt, and Akt, in human leukemia cells were evaluated using Western blotting. Results: Hesperetin dose-dependently inhibited leukemia cell viability. However, we found a low degree of apoptosis and cell cycle arrest induced by hesperetin in U937 cells. These findings imply the presence of additional mechanisms modulating hesperetin-induced cell death. Next, we evaluated autophagy, the possible mechanism modulating cell death or survival, to clarify the underlying mechanism of hesperetin-induced cell death. Hesperetin also dose-dependently increased the ratio of LC3II/I, Atg5, and Beclin 1 and decreased p62. Moreover, 3-methyladenine (3-MA) and bafilomycin A1 (Baf-A1) inhibited hesperetin-induced autophagy. We suggest that hesperetin can protect cancer cells during the transient period and may extend survival. Furthermore, a decrease in p-mTOR and p-Akt expression and an increase in p-AMPK expression were observed. Collectively, these findings suggest that hesperetin induces autophagy by modulating the AMPK/Akt/mTOR pathway. Conclusion: Hesperetin promoted cell death in the human leukemic cell line U937 by inducing a low degree of slight apoptosis, cell cycle arrest, and autophagy. It is therefore a potential adjuvant to antileukemia therapy and may be combined with other chemotherapeutic drugs to reduce chemoresistance and side effects.